EMPODERAMENTO: POSSIBILIDADES DA PRÁTICA PROFISSIONAL NOS CENTROS DE REFERÊNCIA DE ASSISTÊNCIA SOCIAL EM PONTA GROSSA-PR - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2011)
This research aims to reflect on the limits and the possibilities of the professional practice of the interdisciplinary team of the Social Assistance Reference Centers - SARC contributes for the aiding of the process of empowerment of the assisted families in this institution. It is about qualitative research, whose empirical context was the situated SARC in the city of Ponta Grossa, Paraná State. The research was developed through the following methodological procedures: bibliographical revision, documentary study, comment, half-structuralized interview with professionals of Social Service, Psychology and Pedagogy, and analysis of depositions having as reference the central categories of the research, which are: empowerment, family, social assistance, professional practice and interdisciplinary team. The National Politics of Social Assistance of 2004 emphasizes that the work, which is carried through with families must have a social vision that not only privileges the situations of social, economic and cultural vulnerabilities that the reality presents to the same ones, but the potentialities must be privileged that these families present regarding to the development of its autonomy. To develop actions that stand out the potentialities is a work that implies in the process of empowerment. In order to accomplish this process, it needs to be considered from the assumptions of the dialogic. According to Paulo Freire the dialogue is basic to exceed the conception that assumes that the empowerment is limited to the mere mechanical acquisition of knowledge. The research concludes that: there is the necessity of investment in the continued formation of the professionals who act in the SARC with the familiar demands in a interdisciplinary perspective; that the offered conditions of work to the teams of the SARC limit its intervention, because they make it difficult the establishment of bonds of the team with the families, regarding that the presented circumstances of work, some professionals do not remain in the institution, this generates a rotation among them, this way, weakening the work with the families. About the possibilities of the empowerment process, we observe that it needs to be mediated by the dialogical action and social-educative actions and its results, as the dialogical process, as the social-educative actions involve information and participation, elements that have the possibility to facilitate the stimulation of the protagonism of the individual and consequently to favor the empowerment.
Keywords: assistência social; empoderamento; família; prática profissional e equipe interdisciplinar; social assistance; empowerment; family; professional practice and interdisciplinary team; CNPQ::CIENCIAS SOCIAIS APLICADAS